Investigation of intralayer and interlayer shear properties of stabilized rammed earth by direct shear tests. (27th February 2023) - Zhou, Tiegang; Zhang, Huiyuan; Zhang, Zaiyu; Zhang, Liangyi; Tan, Wei
Highlights: The causes of slip cracking at the interlayer interface of rammed earth were investigated. Intra- and inter-layer stress-displacement models for rammed earth were proposed. The inter- and intra-layer shear parameters of the stabilized rammed earth were determined. The formulas of compressive strength and interlayer shear strength of rammed earth under different normal stresses were proposed. Abstract: Rammed earth construction has attracted a lot of attention because of its unique advantages of energy saving, environmental protection, low cost, easy access to materials, and suitability for living. Due to the special layered segmental ramming process, the distribution of rammed earth is superimposed, which makes the rammed earth walls have many weak horizontal interfaces. The failure mode of many post-earthquake rammed earth buildings is mainly in the form of shear failure, and the slip failure at the interface of adjacent rammed layers is particularly serious. There is a lack of research on the cracking and slip phenomena between rammed earth layers and the shear parameters between and within rammed earth layers. In this study, the interlayer and intralayer shear behavior of rammed earth were compared in four aspects: failure phenomenon, shear stress-displacement curve, cohesion and internal friction angle, and shear modulus, using normal stress, additive type, and additive content as variables. The causes of slip failure easily occurring at the interlayer interface were investigated. The interlayer interface and intra-layer shear failure laws of unstabilized and stabilized rammed earth were explored. The compressive strength was used to predict the interlayer shear strength. The shear resistance parameters of unstabilized and stabilized rammed earth were determined to provide data for future measures to enhance the optimization of the interlayer interface. The results showed that the interlayer failure of rammed earth was mainly caused by the lack of cohesion of the soil at the interlayer interface, and the interlayer cohesion was 24%-45% of the intra-layer cohesion. The interlayer interface shear strength was about 35%-84% of the intra-layer shear strength.